AN ANALYSIS OF DETERMINANTS OF E-COMMERCE-BASED ACCOUNTING INFORMATION SYSTEMS ADOPTION ON THE PERFORMANCE OF MILLENNIAL MSME IN MEDAN CITY - Syah, Dedy Husrizal; Karen, Abigail El (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2022)
This study aims to determine the effect of perceived usefulness, perceived ease of use, attitude toward using, and behavioral intention to use the service of e-commerce-based accounting information systems on Millennial MSME performance. The population in this research were all Millennial MSME actors in Medan City. The research sample comprised 46 respondents from this population using the purposive sampling method. According to the findings of this research, perceived usefulness has a positive and significant effect on MSMEs' performance, perceived ease of use has no significant effect on MSMEs' performance, attitude toward using has no significant effect on MSMEs' performance, and behavioral intention to use has no significant effect on MSMEs' performance. However, perceived usefulness, perceived ease of use, attitude toward using, and behavioral intention to use all significantly impact MSMEs' performance. This research highlights the effectiveness of MSME technology acceptance in adopting e-commerce and provides an overview of the condition of MSMEs amid technological advances, as well as empirical evidence to carry out further guidance for MSME actors.